Integrating Content and Structure Aspects of the Self: Traits, Values, and Self‐Improvement. Issue 2 (14th June 2013) - Roccas, Sonia; Sagiv, Lilach; Oppenheim, Shani; Elster, Andrey; Gal, Avigail
Abstract Research on the structure of the self has mostly developed separately from research on its content. Taking an integrative approach, we studied two structural aspects of the self associated with self‐improvement—self‐discrepancies and perceived mutability—by focusing on two content areas, traits and values. In Studies 1A–C, 337 students (61% female) reported self‐discrepancies in values and traits, with the finding that self‐discrepancies in values are smaller than in traits. In Study 2 (80 students, 41% female), we experimentally induced either high or low mutability and measured perceived mutability of traits and values. We found that values are perceived as less mutable than traits. In Study 3, 99 high school students (60% female) reported their values, traits, and the extent to which they wish to change them. We found that values predict the wish to change traits, whereas traits do not predict the wish to change values. In Study 4, 172 students (47.7% female) were assigned to one of four experimental conditions in which they received feedback denoting either uniqueness or similarity to others, on either their values or their traits. The results indicated that feedback that one's values (but not traits) are unique affected self‐esteem. Integrating between theories of content and structure of the self can contribute to the development of both.